An Assessment Study of the Communication Strategies used by multi - level marketing companies in the Philippines - Cajanding, Caren, Toribio, Paulette Diane and Villanueva, Roberta Mara. 4 0 16; 5 (2010)
u
Undergraduate Thesis> (Bachelor in Mass Communication)- Pamantasan ng Lungsod ng Maynila, 2010.
Keywords: 2 -- 0; 6; 20; 20; 2